Out-of-pocket expenses incurred by patients obtaining free breast cancer care in Haiti. (27th April 2015) - O'Neill, Kathleen M; Mandigo, Morgan; Pyda, Jordan; Nazaire, Yolande; Greenberg, Sarah L M; Gillies, Rowan; Damuse, Ruth
Abstract: Background: Women with breast cancer in low-income and middle-income countries (LMICs) account for 51% of cases globally and often present with advanced disease. Fear of costs contributes to delay in seeking care, as health expenditures are financially catastrophic for families worldwide. Despite efforts to improve affordability of health care in LMICs, the financial burden of indirect costs (eg, transportation and lost wages) is often overlooked. We aimed to identify and quantify the expenditures of patients seeking breast cancer care in a LMIC. Methods: Patients receiving breast cancer care free of charge at Hôpital Universitaire de Mirebalais (HUM) in Haiti were interviewed to quantify their costs and assess the effect of these costs on patients and families. These costs included expenses for food, lodging, transportation, childcare, medical costs at other institutions, and lost wages. 61 patients were interviewed during diagnostic, chemotherapy, and surgical visits between March 1, and May 12, 2014. Institutional review board exemption was granted from Boston Children's Hospital and Partners in Health/Zanmi Lasante. Findings: The median non-medical out-of-pockent expenses incurred by breast cancer patients at HUM were US$233 (95% CI 170–304) for diagnostic visits, US$259 (95% CI 200–533) for chemotherapy, and US$38 (95% CI 23–140) for surgery. The median total out-of-pockent expense (including medical costs) was US$717 (95% CI 619–1171). These costs forced 52% of participants into debt and 20% to sell possessions. The median percentage of potential individual income spent on out-of-pocket costs was 60%. The median sum of out-of-pocket costs and lost wages was US$2996 (95% CI 1676–5179). Interpretation: In Haiti, 74% of people earn less than US$2 per day. Even when breast cancer treatment is provided for free, out-of-pocket expenses could account for more than 91% of annual earnings at this income level. This financial burden is an overwhelming obstacle for Haiti's poorest citizens, and probably for many patients in LMICs. High-powered, multisite studies are needed to further characterise this burden worldwide. Funders and health-care providers should reduce indirect costs to achieve equitable access to oncology care. Funding: Boston Children's Hospital and Partners in Health.